FACTORES MATERNOS QUE INTERVIENEN EN LA INTERRUPCIÓN DE LA LACTANCIA MATERNA EXCLUSIVA EN UN HOSPITAL PÚBLICO - Juy Mori, María (2017)
Objectives: To identify the maternal factors involved in the interruption of exclusive breastfeeding in the Hermilio Valdizán Hospital of Huanuco. Method: Prospective cases and controls`s study was conducted, through the implementation of a survey 196 women who gave birth in a Public Hospital in the city of Huanuco, whose children turn six months of age in 2010, the variables studied as factors of interruption of the exclusive breastfeeding were: type of childbirth, parity, occupation, perception of the amount of milk produced, puerperal mastitis and early use of formula milk in the hospitals. Results: We analyzed 98 cases and 98 controls, of which was found relationship with the interruption of the exclusive breastfeeding: cesarean delivery (67.2%), mothers working outside the home (100), mothers they perceived as insufficient milk production (100%), early use of formula milk (100); mothers with more than two children (54.8%), with regard to parity and to age group of course greater risk (<18 and >35 years) Not found significant difference; multivariate analysis showed that the puerperal mastitis and the early use of formula milk in the hospital explained in a 98.68% the interruption of exclusive breastfeeding in the population, all of them with IC=95%; p<0.05. Conclusions: Were factors associated with the interruption of the exclusive breast-feeding the puerperal mastitis and the early use of formula milk in the hospitals.